Proceedings of the 2006 International Workshop on Global Software Development for the Practitioner 2006
DOI: 10.1145/1138506.1138524
|View full text |Cite
|
Sign up to set email alerts
|

Global software development in the freeBSD project

Abstract: Freebsd is a sophisticated operating system developed and maintained as open-source software by a team of more than 350 individuals located throughout the world. This study uses developer location data, the configuration management repository, and records from the issue database to examine the extent of global development and its effect on productivity, quality, and developer cooperation. The key findings are that global development allows round-the-clock work, but there are some marked differences between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 25 publications
3
30
1
Order By: Relevance
“…While we draw parallels between OSS and some related research areas in Table 3, it is not an extensive list. Software process improvement [1,65], distributed development [150], global software development [174], and agile development [199] In this review we will consider three ways of using OSS products. OSS products may first of all be deployed as-is without any changes, used as CASE tools in software development, or integrated into other software systems.…”
Section: Related Research Fieldsmentioning
confidence: 99%
See 1 more Smart Citation
“…While we draw parallels between OSS and some related research areas in Table 3, it is not an extensive list. Software process improvement [1,65], distributed development [150], global software development [174], and agile development [199] In this review we will consider three ways of using OSS products. OSS products may first of all be deployed as-is without any changes, used as CASE tools in software development, or integrated into other software systems.…”
Section: Related Research Fieldsmentioning
confidence: 99%
“…Such work can be related to, for instance, software process improvement [1,65]. Other researchers relate the development processes in OSS communities to distributed development [150], global software development [174], and agile methods [199].…”
Section: Related Research Fieldsmentioning
confidence: 99%
“…Because of the correlation between performance and quality, Ramasubbu and Balan found that dispersion of sites had an indirect effect on quality. However, Spinellis (2006) and Bird et al (2009) report contradicting results. Spinellis (2006) found that geographical dispersion of developers had a negligible effect on productivity and quality in their studied case.…”
Section: Related Workmentioning
confidence: 93%
“…However, Spinellis (2006) and Bird et al (2009) report contradicting results. Spinellis (2006) found that geographical dispersion of developers had a negligible effect on productivity and quality in their studied case. Spinellis used adherence, or lack there of, of coding style, and defect density as surrogates for quality.…”
Section: Related Workmentioning
confidence: 93%
See 1 more Smart Citation